Role of trans rectal and scrotal ultra sonography in male infertility - Kaur Mohi, Jaswinder; Singh Mittal, Manoj; Kaur, Navkiran; Kaur, Amarjit; Garg, Deepak (International Journal of Medical Research and Review, 2018)
Introduction: Investigation of male infertility is assuming greater importance with male factors implicated as the cause in up to half of the infertile couples. This prospective cross-sectional study aims to establish the role of transrectal and scrotal ultrasonography in male infertility. Besides routine investigations trans rectal and scrotal ultra sonography was performed to detect testicular and post-testicular etiology or abnormality. Aims: The aim of this cross-sectional study was to determine the role of transrectal and scrotal ultrasonography in the evaluation of male infertility and to compare the findings of ultrasonography with clinical and surgical findings. Material and Methods: The prospective cross-sectional study was carried out on 50 patients visiting the ultrasound section of Rajindra Hospital; Patiala with complaint of infertility over the span of 2 years. All the patient undergoes transrectal and scrotal ultrasonography with high frequency transducer having a frequency of 7.5 MHz and Color Doppler wherever indicated. Results: Ultra sonographic findings of scrotum in 50 patients reveals 24 cases of varicocele, 7 cases of epididymal cysts, 8 cases of hydrocele, 3 cases of epididymitis, 2 cases of cryptorchidism, 2 cases of testicular microlithiasis and 1 case of bilateral testicular cyst. Apart from the patient who had cryptorchidism, the testis of all the patients were normal in size, site, shape and echo pattern. The clinical palpation when compared to ultrasound was found to be have a sensitivity of 58.33% and a specificity of 92.31%. The positive predictive value was found to be 87.50% and negative predictive value 70.59%. Conclusion: Trans rectal and scrotal ultrasound provides valuable information in the diagnostic evaluation of infertile men and substantially more pathological conditions can be detected on ultrasound compared to clinical palpation.